Health problems and help-seeking in a nationwide sample of operational Norwegian ambulance personnel - Ekeberg Øivind; Hem Erlend; Sterud Tom; Lau Bjørn (BMC, 2008)
Abstract Background To estimate the prevalence of anxiety and depression symptoms, and their association with professional help-seeking, among operational ambulance personnel and a general working population, and to study the symptoms of musculoskeletal pain and disturbed sleep among ambulance personnel. Methods The results of a comprehensive nationwide questionnaire survey of operational ambulance personnel (n = 1180) were compared with the findings of a population-based Norwegian health study of working people (n = 31,987). The questionnaire included measures of help-seeking, the Hospital Anxiety and Depression Scale, the Subjective Health Complaints Questionnaire, the Karolinska Sleep Questionnaire and the Need for Recovery after Work Scale. Results Compared with those in the reference population, the mean of level anxiety symptoms in the ambulance sample was lower for men (3.5 vs. 3.9, P <0.001) and women (4.0 vs. 4.4, P <0.05), and the mean level of depression symptoms in ambulance workers was lower for men (2.3 vs. 2.8, P <0.05) but not for women (2.9 vs. 3.1, P = 0.22). A model adjusted for anxiety and depression symptoms indicated that ambulance personnel had lower levels of help-seeking except for seeing a chiropractor (12% vs. 5%, P <0.01). In the ambulance sample, symptoms of musculoskeletal pain were most consistently associated with help-seeking. In the adjusted model, only symptoms of disturbed sleep were associated with help-seeking from a psychologist/psychiatrist (total sample = 2.3%). Help-seeking was more often reported by women but was largely unaffected by age. Conclusion The assumption that ambulance personnel have more anxiety and depression symptoms than the general working population was not supported. The level of musculoskeletal pain and, accordingly, the level of help-seeking from a chiropractor were higher for ambulance workers. More research should address the physical strains among ambulance personnel.